Anthesis, the infectious process and disease progress curves for fusarium head blight in wheat - Reis,Erlei Melo (2016)
ABSTRACT Fusarium head blight of wheat (Triticum aestivum), caused by the fungus Gibberella zeae, is a floral infecting disease that causes quantitative and qualitative losses to winter cereals. In Brazil, the sanitary situation of wheat has led to research in order to develop strategies for sustainable production, even under adverse weather conditions. To increase the knowledge of the relationship among the presence of anthesis, the infectious process, the disease progress and the saprophytic fungi present in wheat anthers, studies were conducted in the experimental field of University of Passo Fundo (UPF), using the cultivar Marfim, in the 2011 growing season. The disease incidence in spikes and spikelets was evaluated. The presence of exserted anthers increased the spike exposure time to the inoculum. The final incidence of fusarium head blight, in the field, was dependent on the presence of exserted anthers. The disease followed an aggregation pattern and its evolution increased with time, apparently showing growth according to secondary cycles. The fungi isolated from exserted anthers (Alternaria sp., Fusarium sp., Drechslera spp. and Epicoccum sp.) did not compete for the infection site of fusarium head blight in wheat, not interfering with the incidence of F. graminearum.